Next-Generation Metagenome Sequencing Shows Superior Diagnostic Performance in Acid-Fast Staining Sputum Smear-Negative Pulmonary Tuberculosis and Non-tuberculous Mycobacterial Pulmonary Disease - Xu, Peng; Yang, Ke; Yang, Lei; Wang, Zhongli; Jin, Fang; Wang, Yubao; Feng, Jing (Frontiers in Microbiology, 2022)
In this study, we explored the clinical value of next-generation metagenome sequencing (mNGS) using bronchoalveolar lavage fluid (BALF) samples from patients with acid-fast staining (AFS) sputum smear-negative pulmonary tuberculosis (PTB) and non-tuberculous mycobacterial pulmonary disease (NTM-PD). Data corresponding to hospitalized patients with pulmonary infection admitted to the hospital between July 2018 and July 2021, who were finally diagnosed with AFS sputum smear-negative PTB and NTM-PD, were retrospectively analyzed. Bronchoscopy data as well as mNGS, Xpert, AFS (BALF analysis), and T-SPOT (blood) data, were extracted from medical records. Thereafter, the diagnostic performances of these methods with respect to PTB and NTM-PD were compared. Seventy-one patients with PTB and 23 with NTM-PD were included in the study. The sensitivities of mNGS, Xpert, T-SPOT, and AFS for the diagnosis of PTB were 94.4% (67/71), 85.9% (61/71), 64.8% (46/71), and 28.2% (20/71), respectively, and the diagnostic sensitivity of mNGS combined with Xpert was the highest (97.2%, 67/71). The specificity of Xpert was 100%, while those of AFS and T-SPOT were 73.9% (17/23) and 91.3% (21/23), respectively. Further, the 23 patients with NTM-PD could be identified using mNGS, and in the population with immunosuppression, the sensitivities of mNGS, Xpert, T-SPOT, and AFS were 93.5%, 80.6%, 48.4%, and 32.3%, respectively, and the diagnostic sensitivity of mNGS combined with Xpert was the highest (100%, 31/31). The specificities of Xpert and T-SPOT in this regard were both 100%, while that of AFS was 40% (2/5). Furthermore, using mNGS, all the NTM samples could be identified. Thus, the analysis of BALF samples using mNGS has a high accuracy in the differential diagnosis of MTB and NTM, and mNGS combined with Xpert can improve the detection of MTB, especially in AFS sputum smear-negative patients with compromised immune states or poor responses to empirical antibiotics.